Once More on Mk 16.9-20 - ALEXEEV, Anatoly A. (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
For the diaspora and the first pagan Christians, Galilee was not an authoritative centre of the Hellenistic era, therefore, in the accounts of the Resurrection of Jesus Christ, this event is either simply transferred to Jerusalem (Luke) or separated from the main text by a colophon (John) or questioned in parts of the manuscript tradition (Mark), which influences the modern criticism.